Research and Educational Federation Testbed: A New Architecture Design for the Collaborative Research Cloud - Mahmoud A. Mahdi; Omar S. Mossad; Mustafa ElNainay (International Telecommunications Society (ITS), 2019)
We present a new architecture design with implementation to handle the unified testbed federation System, created initially for all the faculties and research centers in Egypt. It is based on self-management testbed with synchronize data and shared interfaces. The architecture includes the functions required to enable, manage and control testbeds over multiple sites for research and educational purposes. The main target of this research is to propose an architecture for the federation of Internet experimentation facilities, which extends across a diverse research community. This paper comes out of Collaborative Research Cloud (CRC) project funded by the National Telecommunications Regulatory Authority to create a unified testbed federation system to allow for remote access for existing research equipment in some faculties and research centers in Egypt as a bootstrapping to apply it later to all other research centers in Egypt. The main target of CRC project is to build a system that allocate resources to the authenticated users, keep track of system resources, and be accessed only by the authorized user. This paper presents the new architecture design for the federated testbed which includes the structure design, and implementation techniques of the main modules. The federation architecture is also designed with flexibility for further development and/or modification. The main federation system is divided into manageable processes that are grouped to sub-modules and modules that are built with abstraction.
Keywords: 330